Native American gene continuity to the modern admixed population from the Colombian Andes: Implication for biomedical, population and forensic studies. (September 2018) - Criollo-Rayo, Angel A.; Bohórquez, Mabel; Prieto, Rodrigo; Howarth, Kimberley; Culma, Cesar; Carracedo, Angel; Tomlinson, Ian; Echeverry de Polnaco, Maria M.; Carvajal Carmona, Luis G.; ,
Highlights: MtDNA suggest a pre/post Columbian genetic continuity in the Colombian Andes. Y-chromosome diversity follows a clinal gradient in the studied region. Sex-biased/male-driven admixture process, involving Pijao women with European men. Admixed closer to Indigenous resguardos have a higher Native American ancestry. Abstract: Andean populations have variable degrees of Native American and European ancestry, representing an opportunity to study admixture dynamics in the populations from Latin America (also known as Hispanics). We characterized the genetic structure of two indigenous (Nasa and Pijao) and three admixed (Ibagué, Ortega and Planadas) groups from Tolima, in the Colombian Andes. DNA samples from 348 individuals were genotyped for six mitochondrial DNA (mtDNA), seven non-recombining Y-chromosome (NRY) region and 100 autosomal ancestry informative markers. Nasa and Pijao had a predominant Native American ancestry at the autosomal (92%), maternal (97%) and paternal (70%) level. The admixed groups had a predominant Native American mtDNA ancestry (90%), a substantial frequency of European NRY haplotypes (72%) and similar autosomal contributions from Europeans (51%) and Amerindians (45%). Pijao and nearby Ortega were indistinguishable at the mtDNA and autosomal level, suggesting a genetic continuity between them. Comparisons with multiple Native American populations throughout the Americas revealed that Pijao, had close similarities with Carib-speakers from distant parts of the continent, suggesting an ancient correlation between language and genes. In summary, our study aimed to understand Hispanic patterns of migration, settlement and admixture, supporting an extensive contribution of local Amerindian women to the gene pool of admixed groups and consistent with previous reports of European-male driven admixture in Colombia.